Genotypic variation in adaptation to soil acidity in local upland rice varieties - Suwannee Laenoi (2018)
© 2014 NIAB. Local upland rice germplasm is an invaluable resource for farmers who grow rice on acidic soils without flooding that benefits wetland rice. In this study, we evaluated the adaptation to soil acidity in common local upland rice varieties from an area with acidic soil in Thailand. Tolerance to hydrogen and aluminium (Al) toxicity was determined by measuring root growth, plant dry weight and phosphorus (P) uptake in aerated solution culture without the supplementation of Al (0 mg/l) at pH 7 and 4 and with the supplementation of 10, 20 and 30 mg Al/l at pH 4. The root growth of upland rice plants grown from farmers' seed was depressed less by Al than that of common wetland rice varieties. Pure-line genotypes of upland rice varieties were differentiated into several classes of Al tolerance, with frequency distribution of the classes that sometimes differed between the accessions of the same varieties. The effect of Al tolerance on root length was closely correlated with depression by Al in root dry weight and whole-plant P content. A source for adaptation to soil acidity for exploitation in the genetic improvement of aerobic and rainfed rice is clearly found among local upland rice varieties grown on acidic soils. However, the variation in tolerance to soil acidity within and among the seed lots of the same varieties maintained by individual farmers as well as among the varieties needs to be taken into consideration.